The Effects of Isolated Fractions of Mesobuthus eupeus Scorpion Venom on Humoral Immune Response - Mohammad Khosravi; Mansour Mayahi; Farnoosh Kaviani; Mohammad Nemati (Tehran University of Medical Sciences, 2017)
Background: Many elements such as immunosuppressive, chemotactic and anti-inflammatory peptide that could effect on human and animals physiologic system were determined in venom. This study evaluated the use of Mesobuthus eupeus scorpion venom fractions as an immunomodulator. Methods: The venom fractions collected from Khuzestan Province in South West of Iran were purified by ion exchange chromatography. Elution of the bounded elements was done by using a linear gradient of sodium chloride (0.1, 0.25, 0.5, 0.75, 1, 1.25, 1.5 and 2 molar). The fractions were analyzed by Bradford spectrophotometric and SDS-PAGE method. After treatments of chicken with venom fractions and sheep red blood cell (SRBC), direct haemagglutination test in microtiter plate was used for the determination of the chicken SRBC antibody titer. Results: The fraction released by NaCl 1.25M had the highest protein concentration. The highest and lowest antibody titer was determined at the fifth (NaCl 0.75 molar) and seventh fraction (NaCl 1.25 molar), respectively. Conclusion: Different protein profile of isolated fractions, were associated with various effect on immune response. Both enhancing and suppressing of the chicken humoral immune response to SRBC were observed after M. eupeus faction's venom treatment. It is due to biological functions of venom components. Purification of these elements would provide the new agents for immune responses manipulation.